Discussion on industrial Internet data security solution - Zhu Lifeng (Dianzi Jishu Yingyong, 2022)
This article introduced our country industry development present situation，analyzed the problems of industrial Internet data security from both international and domestic aspects, and put forward solution for industrial Internet data security from the implementation of safety laws and regulations, establishing and improving the data security system and establishing an independent and controllable advanced technology system. It provides reference for further improving the level of industrial Internet data security in China.